Mereduksi Waste Pada Proses Produksi tahu di UMKM. XYZ Menggunakan Lean Manufacturing - Hafizh Fikri Kawarizmi; Suseno Suseno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Pak Rahman's tofu factory was established in 2015 and is located at Jalan Raya Karangturi No.RT 07, Manggisan, Baturetno, Banguntapan District, Bantul Regency, Yogyakarta Special Region. The problem experienced is the waste of time in the tofu production process, namely 242.6 seconds for taking firewood at the soybean boiling stage, and 243.2 seconds for taking firewood during the tofu frying process. In addition, there is waste transportation because the factory layout is still inefficient with a distance of 8 and 9 meters for wood collection so that it wastes about 485.8 seconds and the transportation of the grinding process to boiling which is 8 meters away takes 116.2 seconds. Therefore, this study aims to identify the causes of waste and provide suggestions for improvement by applying Lean Manufaturing to eliminate waste that occurs. Based on the results of data processing using Current Value Stream Mapping, it is known that the lead time is 20131.2 seconds, VA is 17785 seconds, NVA is 602 seconds and NNVA is 1744.2 seconds. To minimize waste, an action planning of improvement proposals using 5W + 1H is carried out. The improvement recommendations given to minimize waste transportation and motion are rearranging the layout in the production process area and the design and placement of firewood storage. With this proposed improvement made Future Value Stream Mapping, there are changes in lead time and NVA, lead time decreased to 19758 seconds while NVA time decreased from 602 seconds to 228.75 seconds.